Factors Affecting The Profitability Of Consumer Goods Manufacturing Companies In The 2018-2022 Period - Andra Aprillia Ayu Triana; Amirya, Mirna (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
Profitability reflects the ability of a company to generate profits measured by the companies’ success and management effectiveness. If the company’s profitability is stable, then investors will trust the company and remain interested in continuing to invest. As such, this study quantitatively examines the effect of company size, capital structure, sales growth, and working capital turnover on profitability. The population of this study includes 50 consumer goods manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2022, from which the samples of 13 companies of established criteria are selected through purposive sampling, and 65 secondary data are obtained The results exhibit that company size has no effect on profitability, capital structure has a negative and significant effect on profitability, sales growth has a positive and significant effect on profitability, and working capital turnover has a negative and insignificant effect on profitability.